Efektivitas Pengawasan Internal dan Eksternal dalam Pengelolaan Keuangan Perpajakan di Tingkat Kecamatan - Seiko, Shoonen Matahari; Ardiensyah, Ardiensyah; Nalien, Elvira Mulya (Universitas Pahlawan Tuanku Tambusai, 2025)
Financial management of taxation at the sub-district level requires effective supervision to ensure accountability and transparency in revenue collection and utilization. This study aims to analyze the effectiveness of internal and external supervision in financial management of taxation at the sub-district level based on a literature review from Sinta-indexed journals and trusted sources. The research method uses library research with a descriptive qualitative approach. The findings indicate that internal supervision conducted by sub-district officials and inspectorates plays a crucial role in preventing irregularities and improving financial report quality. External supervision by the Audit Board of Indonesia (BPK) and the community also contributes to transparency and accountability. However, supervision effectiveness is hindered by limited human resources, suboptimal regulations, and lack of community participation. This study recommends enhancing internal supervisors’ capacity, strengthening regulations, and leveraging information technology to support more effective supervision.